Record-efficiency flexible perovskite solar cell and module enabled by a porous-planar structure as an electron transport layer. Issue 12 (29th October 2020) - Chung, Jaehoon; Shin, Seong Sik; Hwang, Kyeongil; Kim, Geunjin; Kim, Ki Woong; Lee, Da Seul; Kim, Wansun; Ma, Boo Soo; Kim, Young-Ki; Kim, Taek-Soo; Seo, Jangwon
Abstract : Porous planar structure, as a new concept of low temperature processing ETL, enables to achieve unprecedented PCE in flexible unit cells and large area modules. Abstract : A facile and low-temperature process to prepare planar perovskite solar cells (PSCs) has led to considerable progress in flexible solar cells toward high throughput production based on a roll-to-roll process. However, the performance of planar PSCs is still lower than that of mesoscopic PSCs using a high temperature process. Here, we report a new concept of a low temperature processed porous planar electron transport layer (ETL) inspired by a mesoporous structure for improving the performance of flexible devices. The structurally and energetically designed porous planar ETL induced the formation of a high quality perovskite and a preferred band alignment, resulting in improved charge collection efficiency in a fabricated device. Through the porous planar ETL, we achieved a power conversion efficiency (PCE) of 20.7% with a certified efficiency of 19.9% on a flexible substrate, which is the highest PCE reported to date. In addition, for the first time, we succeed in fabricating a large area flexible module with the porous planar ETL, demonstrating a PCE of 15.5%, 12.9% and 11.8% on an aperture area of 100 cm 2, 225 cm 2 and 400 cm 2, respectively. We believe that this strategy will pave a new way for realizing highly efficient flexible PSCs.